The Correlation between Intensity of Social Media Use and The Level of Social Anxiety Students - Desi Kurniasari; Rodiyah Soekardi; Dwi Endah Kurniasih; Joko Krisdiyanto (Universitas Respati Yogyakarta, 2023)
Based on data from the Global Web Index in 2022 around the world there are 4.95 billion internet users and 4.62 billion as active social media users with average usage duration of around 3-4 hours per day. Until January 2022, the number of internet users in Indonesia has reached 204.7 million. While the types of social media that are widely used by students are Whatsapp, Instagram, and Tictoc. The results of a preliminary study on students at Respati Yogyakarta University (Unriyo), showed that out of 10 students from the Faculty of Health Sciences (Fikes), 7 students experienced moderate anxiety, and 3 students experienced mild anxiety. To determine the correlation between the intensity of social media use and the level of social anxiety in students. This is quantitative research using a cross sectional approach. This research was carried out at Fikes, Unriyo in December 2022. Sampling was carried out using the accidental sampling technique. Data analysis used Kendall's tau_b correlation test. Most (65%) of respondents have a high intensity of using social media, and most (71%) of respondents experience moderate levels of social anxiety. The Kendall'a tau_b test results obtained a p value of 0.000 (<0.05). Statistically there is a positive correlation between the intensity of social media use and the level of student social anxiety